Reasons for prescription opioid use while playing in the National Football League as risk factors for current use and misuse among former players - Dunne, E. M.; Striley, C. W.; Mannes, Z. L.; Asken, B. M.; Ennis, N.; Cottler, L. B. (Clinical Journal of Sport Medicine, 2020)
Objective: Prescription opioid misuse has become a significant public health issue. Previous research has examined predictors of prescription opioid use and misuse among former National Football League (NFL) players. The present study aimed to describe how reasons for prescription opioid use while in the NFL corresponds to use and misuse in retirement.